Use of the PlantNet Application in Climbing Plant Identification and Students’ Perceived Cognitive Learning Outcomes in a Higher Plant Botany Course - Rahmawati, Syah Fitri; Khairul, Khairul; Siregar, Zunaidy Abdullah (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: Botany learning, particularly plant identification, requires direct observation skills and a strong understanding of morphological characteristics. Mobile-based plant identification applications, such as PlantNet, have the potential to serve as learning support tools. Methods: This study used a quantitative descriptive approach with a non-experimental design. The subjects were 21 Biology Education students at Labuhanbatu University taking the Botany of Higher Plants course. Data were collected using a four-point Likert-type questionnaire to describe students' perceptions of PlantNet use and their perceived cognitive learning outcomes after the vine identification activity. Data were analyzed descriptively using total scores, percentages, and categories. Results: The study found that the use of the PlantNet application was rated very good, particularly for ease of use, clarity of morphological/taxonomic information, and support for the identification process. Students' perceptions of cognitive learning outcomes were also categorized as very good for conceptual understanding, recognition of morphological characteristics, and determining vine classification. Conclusions: These findings indicate that students perceive PlantNet positively as a supportive tool for field observation-based botany learning. However, direct measurement of cognitive learning outcomes is still needed in further research to more strongly demonstrate the influence of application use on academic achievement.